Small Molecules and Porous Silica Nanoparticle Encapsulated Gd(III) and Mn(II) Complexes as MRI Contrast Agents - Mallik, Riya (My University, 2024)
The content of this thesis has been divided into five chapters according to the results of experimental works that have been performed during the research period. Chapter I is the intorductory chapter of the thesis that represents an overview of Gd(III) and Mn (II) based complexex and nanoparticles as alternative MRI contrast agents with enhanced relaxivity and other physiochemical properties to target various endogenous conditions.
Mukherjee, Chandan
Keywords: MRI Contrast Agents; Mn(II)Gd(III) Complex; Porous Silica Nanoparticles; in-vitro and in-vivo Studies